A Study On Practices Of Solid Waste Disposal In Different Countries - Angeline, Debbie Annabelle (Universiti Sains Malaysia, 2021)
Urbanization and population growth have increased the production of solid waste (SW). This has had a significant impact on environmental concerns and economic growth. Thus, the objectives of this research are to determine the distribution of SW in different countries and to compare their SW disposal methods. Additionally, the relative merits and demerits of various SW disposal methods will be evaluated. This study employs a critical evaluation of the literature, in which data are gathered from secondary sources such as books, journals, and periodicals. The first step of research is planning, which entails defining the issue, the scope of the study, and the research goals. The second step entails conducting the study, and the last stage entails documenting the findings. The findings of this research indicate that Japan, Singapore, and South Korea have comprehensive waste management policies that focus primarily on reducing waste at the source, waste segregation, and waste recycling. As a result, these countries have a high recycling rate, which has resulted in a substantial reduction in the amount of SW disposed of during the final disposal process. Additionally, these countries rely heavily on incineration as a final disposal method to minimize waste volume and maximize the usage of waste-to-energy technology. Malaysia, Vietnam, and India, on the other hand, do not conduct waste reduction at the source, resulting in a significant amount of waste being dumped in landfills. In the context of environmental sustainability and efforts to decrease SW production, it is critical to develop systems that effectively reduce waste creation and improve its recycling rate. Japan, South Korea, and Singapore have effectively developed and managed their SW disposal systems in this regard.